2015
DOI: 10.1007/s11920-015-0550-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of Delirium in Palliative Care: a Review

Abstract: Delirium is a complex but common disorder in palliative care with a prevalence between 13 and 88 % but a particular frequency at the end of life (terminal delirium). By reviewing the most relevant studies (MEDLINE, EMBASE, PsycLit, PsycInfo, Cochrane Library), a correct assessment to make the diagnosis (e.g., DSM-5, delirium assessment tools), the identification of the possible etiological factors, and the application of multicomponent and integrated interventions were reported as the correct steps to effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 100 publications
0
50
1
6
Order By: Relevance
“…17 Between 30-50% of delirious episodes are precipitated by potentially reversible causes including infection, faecal or urinary retention, electrolyte imbalances and medications (toxicity or withdrawal). 18 These reversible causes should be sought, reversed if appropriate, and non-pharmacological treatments optimised. 19 Traditional clinical management of symptomatic hyperactive delirium has included both antipsychotics and benzodiazepines (especially in severe cases where the patient is a risk to themselves or others).…”
Section: Deliriummentioning
confidence: 99%
“…17 Between 30-50% of delirious episodes are precipitated by potentially reversible causes including infection, faecal or urinary retention, electrolyte imbalances and medications (toxicity or withdrawal). 18 These reversible causes should be sought, reversed if appropriate, and non-pharmacological treatments optimised. 19 Traditional clinical management of symptomatic hyperactive delirium has included both antipsychotics and benzodiazepines (especially in severe cases where the patient is a risk to themselves or others).…”
Section: Deliriummentioning
confidence: 99%
“…Patients with cancer are at particular risk of developing delirium for a number of reasons, including exposure to certain drugs (opioids, corticosteroids and benzodiazepines) (Gaudreau, Gagnon, Harel, Roy, & Tremblay, 2005), and the presence of bone metastases and haematological malignancies (Ljubisavljevic & Kelly, 2003). In a recent literature review, it was concluded that there needs to be a greater understanding of delirium in palliative care, including its pathophysiology and causation, as well as its treatment (Grassi et al, 2015). and that bowel movements are monitored.…”
Section: Lawley and Hewisonmentioning
confidence: 99%
“…The antipsychotics are commonly used to treat delirium in clinical settings and in PC. Several metaanalyses have shown that antipsychotics are effective treatments for delirium 45,46 (Table 4).…”
Section: -30mentioning
confidence: 99%